2011
DOI: 10.5251/ajsir.2011.2.6.834.845
|View full text |Cite
|
Sign up to set email alerts
|

Environmental pollution and remediation: challenges and management of oil Spillage in the Nigerian coastal areas

Abstract: This paper examines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Corrosion of pipelines and tankers, sabotage and oil production operations accounts for 50%, 36% and 6.5% of oil spill incidence in Nigeria [1]. Generally, oil spills is a big threat to the environment in producing region because it can lead to accumulation of toxic substances such as heavy metals into the environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion of pipelines and tankers, sabotage and oil production operations accounts for 50%, 36% and 6.5% of oil spill incidence in Nigeria [1]. Generally, oil spills is a big threat to the environment in producing region because it can lead to accumulation of toxic substances such as heavy metals into the environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…According to Iniaghe et al (2013), Nwilo and Badejo (2005), about 50%, 28%, 21% and 1% of oil spills are due to corrosion, sabotage, oil production and mechanical problems (including failure of engineering drills and machines, inability to effectively control oil well, and inadequate care in loading and unloading of oil vessels) respectively. Similarly, Adelana et al (2011) reported that corrosion of pipelines and tankers, sabotage and oil production operations accounts for 50%, 36% and 6.5% oil spill incidence in Nigeria.…”
Section: Fire Resulting From Oil Spillsmentioning
confidence: 99%
“…For instance, in 1999 Jesse community of Delta State (Ambe et al, 2015), Nembe/Brass in Bayelsa state and several others in the Niger Delta region, experienced the loss of lives due to fires from spill. In extension, Nigeria's oil line explosion killed over 200 people in Lagos state (Adelana et al, 2011).…”
Section: Fire Resulting From Oil Spillsmentioning
confidence: 99%
“…In-situ bioremediation is carried out at the site of interest whereas in ex-situ bioremediation, the contaminated soil is collected and processed at an offsite area such as a laboratory for cleansing [2]. The main procedure frequently used in oil-spill bioremediation technique is biostimulation, that is, through the addition of nutrients (nitrogen, phosphorus, and potassium) and regulation of environmental conditions to maximize growth of native bacteria and biological degradation.…”
Section: Introductionmentioning
confidence: 99%